Analysis on the Incidence, Staging and Treatment of Carcinoma Cervix at Delta Medical College and Hospital of Bangladesh - Banu, Parvin A; Rukhsana, Naheed; Yasmin, Jebunnessa; Nahar, Lutfun; Malik, Sadiqur R (Delta Medical College Journal, 2013)
Background: Cervical cancer remains the most common cancer among women in this part of the world. Bangladesh has the highest level of incidence and mortality rates due to cervical cancer among women. Cervical cancer is a preventable disease by screening and treatment of pre-invasive condition. Unfortunately, there is no effective screening program in Bangladesh. Objective: The objective was to analyze the clinico-pathologic characteristics and, subsequently the therapy delivered to the patients. Materials and method: This cross sectional study was done from January to December 2011 in oncology division of Delta Medical College and Hospital, Dhaka, Bangladesh. During this period a total of 2264 female carcinoma patients were registered. Out of them 523 patients were with the diagnosis of carcinoma of cervix. Evaluation and characterization of patients with carcinoma cervix were done according to the age group, clinical stages and surgical status. External beam radiotherapy (EBRT) and doses, brachytherapy doses and fractions, time interval between EBRT and brachytherapy, neo-adjuvant and concurrent chemotherapy status were the factors taken into consideration for the analysis of treatment of these patients. Results: The study revealed that the incidence of carcinoma cervix was 23% and highest incidence was between 40-50 years of age group, most of the patients were in Stage IIB (34%) and IIIB (28%) and 31% with unknown stage. About 44% patients were referred postoperatively and most of them with unknown stage. Almost 90% patients received EBRT, 24% patients received concurrent chemo-radiation, 46% of them completed 5 cycles of concurrent chemotherapy and 8.6% patients received neo-adjuvant chemotherapy. About 69% patients received brachytherapy with HDR Co-60 sources and 23% of patients received their brachytherapy treatment after 12 weeks of completion of EBRT. Conclusion: Lack of proper clinical evaluation and documentation, delay in referral and lack of implementation of a standard protocol for the treatment of carcinoma cervix are the major obstacles in our country. DOI: http://dx.doi.org/10.3329/dmcj.v1i2.15915 Delta Med Col J. Jul 2013;1(2):31-36